2D MoSe2/CoP intercalated nanosheets for efficient electrocatalytic hydrogen production. (31st July 2020) - Zhang, Linfei; Zhu, Jingting; Wang, Zhuo; Zhang, Wenjing
Abstract: Low-dimensional transition metal dichalcogenides, e.g., MoSe2, are attractive electrocatalysts for hydrogen evolution reactions (HER). However, the stable 2H-phase MoSe2 with semiconducting properties exhibits electrocatalytic performance only at its sheet edges, but the basal planes without defects are inactive, limiting their performance in HER. This work reported a strategy for comprehensive activation of TMDs by intercalating 2D MoSe2 with 2D CoP. Its unique sandwiched structure opens up activity between the layers, enhancing active surface area to 10-fold. Meanwhile, the maximized interfaces enable rapid ion/electron transport and excellent electrical conductivity, thus yielding superior HER activity. It exhibits a very low overpotential of 105 mV at 10 mA cm −2, small Tafel slope of 51 mV dec −1 and excellent electrochemical stability for >24 h. The CoP significantly increases the hydrogen adsorption sites of MoSe2 in the basal planes, and the P atoms enable Mo and Co atoms adjacent to them become the most active ones, according to Density Functional Theory calculations. Our work, using two layered materials as precursors to intercalate with each other, provides new ideas for designing efficient and non-precious metal electrocatalysts. Moreover, this method can be universally applicable to synthesize other hybrid materials such as CoSe2 /MoSe2, FeP/MoSe2, NiP/MoSe2, CoSe2 /WS2, FeP/TiS2 and so on. Graphical abstract: Image 1 Highlights: 2D MoSe2 /CoP intercalated nanosheets activate the inert basal plane of MoSe2 . The interfaces enable rapid ion/electron transport, thus yielding superior HER activity. P atom enable Mo, Co atom adjacent to them become active centers, according to DFT calculations.